Straits Settlements Blue Book (imports/exports) 1904-1905 vol. 1904-1905 (Great Britain : Public Record Office, 1971)
Mengandungi'Straits Settlements return of imports and exports for the year 1904 & 1905';'Recapitulatory and comparative statement of the value of imports into and exports from the Colony of the Straits Settlements for the year 1903 and 1904, 1904 and 1905';'Blue Book for the year 1905'.